Successful Integrated Coastal Zone Management (ICZM) Program Model of a Developing Country (Xiamen, China) – Implementation in Bangladesh Perspective - Islam, Kazi Shakila; Xue, Xiong-zhe; Rahman, Mohammed Mahabubur (Journal of Wetlands Ecology, 2009)
This paper represents the overall current situation of two Integrated Coastal Zone Management (ICZM) programs- one is as a successful model like Xiamen ICZM program in China and another is as a developing project like ICZM program in Bangladesh. The paper begins with an attempt to track the evolution of policies and their implementation on coastal zone management with particular reference from both the countries. It then discusses the coastal management and livelihood issues that predicate the different socio-economic and environmental situation between the two countries. The paper then goes on to discussion how the institutional management and policy initiatives of Xiamen ICZM have dealt with in the perspective of Bangladesh. There is a brief consideration of the progress of the management for ICZM of Bangladesh and how this project might be more effective and beneficial for Bangladesh. Key words: Integrated coastal zone management, Socio-economic, Bangladesh, Institutional management DOI: 10.3126/jowe.v2i1.1854 Journal of Wetlands Ecology, (2009) vol. 2, pp 34-40